An Ambassador for Neural Networks - Grier, David Alan (Computer (Long Beach, Calif.), 2020)
Neural networks were never a new part of computing, but at one point they needed a dedicated ambassador to move them into computing practice.We should not be surprised to find a tutorial on artificial neural networks in the list of Computer’s most influential articles. Neural networks are now a common subject in computer science, and they have been taught to two or three generations of undergraduates. They would be an obvious topic for a clear and well-organized article, such as the one written by Anil K. Jain, Jianchang Mao, and K.M. Mohiuddin. This article ranks number 30 on on the list of the most influential articles that have been published by Computer. It has 5,128 downloads and 740 citations. Yet, there are several surprises in the article that help us understand both its position in the body of knowledge and the role of Computer in building that body of knowledge. Perhaps the prominent surprise is that the article has never been cited by another article in Computer, the publication that brought it to the field.